Hubungan antara Self Regulated Learning dengan Prokrastinasi Akademik - Noviyanti Noviyanti; Yusmansyah Yusmansyah; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem in this research is academic procrastination behavior. This study aims to find out how is a significant negative correlation between self regulated learning with academic procrastination using quantitative research methods. The sample of this study was 104 students. The instrument used a scale of self regulated learning and academic procrastination scale. The analysis technique used the product moment technique with a significance level of 5%. Based on the analysis, it is known that the value of r-count = -0.810 from the level of r-table = 0,1622. The results of this study indicate that there is a significant negative relationship between self regulated learning and academic procrastination, meaning that the higher the self regulated learning, the lower the academic procrastination in students, and vice versa is the lower the self regulated learning so the higher academic procrastination for students.Masalah dalam penelitian ini adalah perilaku prokrastinasi akademik. Penelitian ini bertujuan untuk mengetahui bagaimanakah hubungan yang signifikan negatif antara self regulated learning dengan prokrastinasi akademik menggunakan metode penelitian kuantitatif. Sampel penelitian ini berjumlah 104 siswa. Instrumen penelitian menggunakan skala self regulated learning dan skala prokrastinasi akademik. Teknik analisa menggunakan teknik product moment dengan taraf signifikansi 5%. Berdasarkan hasil analisa diketahui nilai r-hitung = -0,810 dari taraf r-tabel = 0,1622. Hasil penelitian ini menunjukkan terdapat hubungan yang signifikan negatif antara self regulated learning dengan prokrastinasi akademik, artinya semakin tinggi self regulated learning maka semakin rendah prokrastinasi akademik pada siswa, begitu juga sebaliknya yaitu semakin rendah self regulated learning maka semakin tinggi prokrastinasi akademik pada siswa.Kata kunci: bimbingan konseling, prokrastinasi akademik, self regulated learning